4x + 4y = 4
Divide both sides by 4:
x + y = 1
Subtract y from both sides:
x = y  1
This (y 1) is the value of x you can use for substitution.
The second equation was:
4x  y = 5
Now, substitute (y 1) for x:
4(y 1)  y = 5
Remove the parentheses:
4y 4 y = 5
5y 4 = 5
Add 4 to both sides:
5y = 9
Divide both sides by 5:
y = 9/5
Plug this value for y back into either of the original equations and solve for x:
4x + 4y = 4
Divide both sides by 4:
x + y = 1
x + 9/5 = 1
Add 9/5 to both sides:
x = 1 + 9/5
x = 4/5
12/26/2013

Kevin F.